Soil Microbial Communities as Indicators of Soil Health - Kennedy, Ann C; Stubbs, L (Annals of Arid Zone, 2016)
Healthy soil supports ecosystem function. The health of arid soils is impacted by disturbances and perturbations, which can influence the physical, chemical and biological components of soil. The health of arid soils can be degraded by erosion, desertification: salinization, sodification and other soil contaminants, all of which influence the soil microbial community. Soil organic matter dynamics, nutrient cycling and soil structure are all influenced by microbial processes and are often negatively affected by management. Soil microbial communities often change more rapidly with management and environment. The soil microbial community is more diverse than any other group of organisms, but we know so little about this diverse genetic resource. The functions of these diverse communities range from nutrient cycling and residue decomposition, to soil structural component, to plant growth effects. Management can have a large effect on microbial processes and community structure. New methods are available or emerging that will enhance our knowledge of what is happening underground. Community and process level studies, as well as investigations at the ecosystem and functional level, are needed to develop management systems that include soil biota for successful sustainable systems. As indicated in this manuscript, research is needed to increase our "understanding of the diversity and function of microbial communities in ecosystems. Investigations will enhance the understanding of microbial diversity and increase our knowledge of the functional roles of microbial communities in ecosystem health and productivity.